2017
DOI: 10.1128/aem.01550-17
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Heat Is a Key Environmental Driver Shaping the Microbial Community of Medium-Temperature Daqu

Abstract: "Daqu" is a saccharifying and fermenting agent commonly used in the traditional solid-state fermentation industry (e.g., baijiu and vinegar). The patterns of microbial community succession and flavor formation are highly similar among batches, yet the mechanisms promoting temporal succession in the Daqu microbial ecology remain unclear. Here, we first correlated temporal profiles of microbial community succession with environmental variables (temperature, moisture, and titratable acidity) in medium temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 39 publications
(38 reference statements)
5
95
0
2
Order By: Relevance
“…Previous studies have found that Bacillus are derived from the tools used to make Daqu . Thermoactinomyces have been reported previously in RSF Daqu and may be derived from the raw materials in Daqu , and microbial exothermy also contributes to make it a dominant genus . Thermoactinomyces produce a rich enzyme system that includes esterase and phosphatase and is likely to be relevant to the formation of flavour compounds in RSF Baijiu .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have found that Bacillus are derived from the tools used to make Daqu . Thermoactinomyces have been reported previously in RSF Daqu and may be derived from the raw materials in Daqu , and microbial exothermy also contributes to make it a dominant genus . Thermoactinomyces produce a rich enzyme system that includes esterase and phosphatase and is likely to be relevant to the formation of flavour compounds in RSF Baijiu .…”
Section: Resultsmentioning
confidence: 85%
“…During Baijiu fermentation microorganisms convert protein into amino acids and starch into glucose, and produce many flavour precursors and flavour components such as esters, pyrazines, aromatic and phenolic compounds. Metabolic heat was a primary endogenous driver to promote Bacillus , which are thermotolerant taxa and commonly found in Daqu . Previous studies have found that Bacillus are derived from the tools used to make Daqu .…”
Section: Resultsmentioning
confidence: 99%
“…The brewing of liquor is a process in which microorganisms use raw materials to produce the metabolites that form flavour substances . There are differences in the microbial species and community structures of different flavour liquors, which is one of the factors affecting the formation of different liquor flavours .…”
Section: Discussionmentioning
confidence: 99%
“…During the fermentation process of Chinese Shaoxing rice wine, ten genera ‐ Bacillus , Leuconostoc , Lactococcus , Weissella , Thermoactinomyces , Pseudomonas , Saccharopolyspora , Staphylococcus , Enterobacter and Lactobacillus ‐ were identified as the main bacteria, with Bacillus and Lactobacillus dominant . Xiao et al reported that metabolic heat was a major driving force promoting the formation of microbiota in medium temperature (MT) Daqu from day 4 to 12. During this period, the heat generated by microbial metabolism (53 to 56°C) within MT Daqu inhibited the growth of most microbes, while thermotolerant taxa including Bacillus , unclassified Streptophyta , Weissella , Thermoactinomyces , Thermoascus , and Thermomyces , survived or continued to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported finding Lactobacillus , Leuconostoc , Weissella , Lactococcus , and Pediococcus in medium temperature Daqu, when investigating the main source of prokaryotic microorganisms in fermented grains of medium temperature Daqu liquor. Xiao et al explored the effects of temperature on the microbial community of medium temperature Daqu. They isolated Lactobacillus, Lactococcus, Leuconostoc, Pediococcus and Weissella , and observed that in the initial fermentation stage (up to day 4), other bacteria could grow rapidly in addition to bacteria such as Leuconostoc .…”
Section: Introductionmentioning
confidence: 99%